Variação temporal e espacial de eventos reprodutivos das aves no Parque Nacional do Viruá-Roraima - Teixeira, Tony Andrey Bichinski (2020)
Reproductive biology can reveal fundamental spatial and temporal patterns to understand bird life strategies. For this purpose, we monitor the reproductive activities of birds in the Viruá National Park (PNV) through active and standardized searches during an annual cycle. To carry out this study we used the 5 x 5 km grid (60 km of trails) installed in the PNV by the Biodiversity Research Program, and monitored by the Long Term Ecological Project Forests of Roraima (PELD FORR). Between March 2019 and February 2020, we sampled 15 750 m transects covering the three main types of vegetation in the PNV (terra firma, campina and igapó forests). In these transects we perform distance sampling, where we measured the distance from observer to each reproductive record, allowing us to model the probability of detection of each record. In addition to these standardized observations, we make opportunistic observations along the trails available in the PNV. This dissertation was organized in two chapters. The first chapter presents all information obtained during sampling, including transects and trails, and aims to understand seasonal and spatial patterns of reproduction, exploring reproductive strategies, such as type and height of nests and number of eggs. The second chapter presents the results from distance sampling in transects, and aims to test the effect of rainfall and the level of flooding on the reproductive pattern of birds. In all, we recorded 161 reproductive events, of 65 bird species, from 26 families. Our results demonstrate that despite having recorded reproductive events in all months of the year, most species and families start their reproduction with the beginning of the rains (May), extending until the beginning of the drought (November). The reproductive patterns found are species-specific, with different species using different periods to reproduce. We recorded four basic types of nests, but only birds that nest in cavities reproduced at all times of the year, suggesting that the type of nest may be a seasonal limiter. The height of the nests varied from zero (ground) to ~ 20m, varying in the different vegetation types; nests in the upland forests were, on average, higher than in the igapó. The number of eggs placed in all environments was approximately two per nest, a relatively low number, typical of tropical species that have low productivity and high parental investment. The standardized sampling presented in chapter 2, indicated that the reproductive cycle of birds is influenced by rainfall: birds begin their reproductive period with the first rains. However, we did not find an effect of the type of habitat or the height flood pulse. This study represents the first of its kind in the northern Amazon and resulted in the discovery of a nest not yet described (Celeus flavus) and the first reproductive evidence in Brazil for 3 species and for the state of Roraima from 44 other bird species. We believe that this study opens new perspectives for the study of the reproductive cycles of birds in the region.